KARAKTERISTIK PENDERITA KUSTA DENGAN KECACATAN DERAJAT 2 DI RS KUSTA ALVERNO SINGKAWANG TAHUN 2010-2013 - Natalia, Diana; A. Rahman, Buchary; Witama, Aji (JURNAL BORNEO AKCAYA, 2015)
Abstract. Leprosy has been a health problem because of the grade 2 disabilities. According to the data from Ministry of Health of Indonesia in 2011, there were 2 052 cases of grade 2 leprosy in Indonesia. Objective of this research is to describe the characteristics of leprosy patients with grade 2 disabilities at Alverno Leprosy Hospital Singkawang in 2010-2013. It was a descriptive study with cross sectional approach. There were 23 samples and most of them were found to be at the age of 15-60 years old, male (83%), graduated from primary school (48%), worked as farmer/fisherman (75%), MB type (65%), had history of type 1 reaction (61%), had neuritis history (83%), had disability on feet (49%), complied to the treatment (83%), the disability was found at the diagnosis (48%), and had the symptoms for more than 1 year (91%). Most of the leprosy patients with grade 2 disabilities were found to be at the productive age (15-60 years), male, worked as farmer/fisherman, graduated from primary school, MB type, had disability on feet, the disability was found at the diagnosis, had history of type 1 reaction and neuritis, complied to the treatment and had the symptoms for more than 1 year.